Estrategias de comunicación corporativa para el posicionamiento de la fanpage, CNEL EP unidad de negocio Bolívar, año 2024 - Arellano Rivera, Edison Giovani (2025)
The research proposes corporate communication strategies to improve the positioning of the CNEL EP Bolívar Business Unit Fanpage in 2024. It recognizes the importance of Facebook for institutional interaction, seeking immediacy, transparency, and closeness in the administration of public service. The analysis of the page revealed deficiencies in the regularity of publications, content variety, and comment management, which hinders the building of lasting relationships with users. To solve this, five key strategies are proposed: an editorial calendar to ensure consistency, the development of accessible and empathetic content (such as testimonials), educational campaigns with visual and interactive formats, local media dissemination, and a monitoring system to evaluate their impact. These actions seek to transform the Fanpage into a more human, practical, and educational communication channel, with the goal of improving the institution's image, generating trust, and strengthening the relationship with the community.